2017
DOI: 10.1093/annweh/wxx065
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Surface Contamination by Antineoplastic Drugs in Italian Hospitals: Performance-Based Hygienic Guidance Values (HGVs) Project

Abstract: Antineoplastic drugs (ADs) will continue to represent a potential risk for personnel involved in the handling of these compounds and great concerns have been raised by the presence of ADs in many surveyed workplaces. Eight hospitals were investigated by means of wipe sampling for surface residue determination. Each wipe sample was tested for five ADs considered suitable exposure markers. Cyclophosphamide (CP), gemcitabine (GEM), 5-fluorouracil (5-FU), platinum-containing drugs (Pt), and epi-doxorubicin (EPI) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 16 publications
2
32
1
Order By: Relevance
“…Finally, in our study surface 5-FU concentrations ranged from below the LOQ to 22.22 ng/cm², which is similar to Kiffmeyer et al (37). Lower ranges were found by Koller et al (27) and Kopp et al (33) (39) used the 90th percentile to propose guidance values for CP (3.6 ng/cm²), 5-FU (1.0 ng/cm²), gemcitabine (0.9 ng/cm²), and platinum (0.5 ng/cm²). Furthermore, Sessink (6) coupled guidance values to actions to be taken to ensure a safe environment.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, in our study surface 5-FU concentrations ranged from below the LOQ to 22.22 ng/cm², which is similar to Kiffmeyer et al (37). Lower ranges were found by Koller et al (27) and Kopp et al (33) (39) used the 90th percentile to propose guidance values for CP (3.6 ng/cm²), 5-FU (1.0 ng/cm²), gemcitabine (0.9 ng/cm²), and platinum (0.5 ng/cm²). Furthermore, Sessink (6) coupled guidance values to actions to be taken to ensure a safe environment.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Hedmer et al [21] reported hygienic guidance values (HGVs) for CP and ifosfamide (IP) in different categories of surfaces for hospital workplaces. Recently, Sottani et al [22] have suggested HGVs for 4 ADs based on the 90th percentile of wipe-sampling data distributions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hedmer et al (27) put forward Hygienic Guidance Values (HGVs) for CP and IP for different categories of surfaces at hospital workplaces. Most recently, Sottani et al (28) have recommended HGVs for four ADs based on the 90 th percentile of wipe-sampling data distributions.…”
mentioning
confidence: 99%